Factors associated with physical activity level among undergraduates in a public university, Selangor, Malaysia - Alhassany, Noor Ahmed Jameel (2020)
Steady increase in prevalence of physical inactivity is becoming a major health problem worldwide. The objective of this cross-sectional study was to determine the factors associated with physical activity among undergraduates in a public university in Selangor, Malaysia. A probability based on cluster sampling procedure was used in this study. The data collection was carried out from September 2018 to November 2018. Physical activity level was assessed using accelerometer, and Global Physical Activity Questionnaire (GPAQ). A set of questionnaires was used to determine sociodemographic characteristic (age, race, gender, educational level, income status, marital status, parent's job, parent's income, parent's education, and ethnic origin), and psychosocial factors (self-efficacy, social support and perceived benefit). Anthropometric measurement was conducted by measuring body weight, height, waist circumference of the respondents. Body weight was measured by using Omron Body Composition Analyzer, while height of the respondents was measured by using Seca Body meter. Dietary intake was assessed using 24 - hours diet recall for two days. A total of 261 bachelor’s degree students (138 males, 123 females),74.3% were in a range of (20-24 years) and 57.1% were Malay and 95.4% were single. Based on GPAQ the highest percentage of respondents (63.2%) were engaged in moderate physical activity, followed by 24.9% intense physical activity, then 11.9% low physical activity. Mean steps per day was 7903±5370 for men and 7327±3438 for women, mean PAL was1.36±0.18 for males and 1.4±0.18 for females. Mean body mass index (BMI) was 23.4±4.6 kg/m², mean total energy intake was lower (2325±384 kcal for male), and higher (2228±385 kcal for female) compared to the Recommended Nutrient Intake (RNI) for Malaysians. Mother allowance income (r=0.129, p<0.05), allowance income per month (r=0.184, p<0.01), friend support (r=0.131, p<0.05), self-efficacy (r=0.17, p<0.01), psychological outlook perceived benefit (r=0.170, p<0.05), social interaction PB (r=0.133, p<0.05), physical performance PB (r= 0.170, p<0.05), and weight (r=0.132, p<0.05) showed a week significant correlation with GPAQ. Physical activity by PAL were significantly correlated with age (r=-0.189, p<0.01), preventive health PB (r=0.133, p<0.05), and average energy expenditure (r=0.607, p<0.01). While physical activity based on steps per day showed a significant correlation with age (r=-0.170, p<0.05), mother’s allowance income (r=-0.194, p<0.05), family support (r=-0.182, p<0.05), energy expenditure (r=0.584, p<0.01), BMR (r=0.153, p<0.05), percentage of protein (r=-0.150, p<0.05), and height (r=0.152, p<0.05). Multivariate analysis in the present study revealed that the significant predictors of GPAQ were self-efficacy (t=1.97, p=0.049) and physical performance perceived benefit (t=3.08, p=0.002). The significant predictors with Physical activity based on accelerometer were age of the subject (t=-2.250, p=0.026) and preventive health perceived benefits (t=2.508, p=0.013). The significant predictors of physical activity according to the steps were age (t=-2.529, p=0.01), family support (t=- 2.058, p=0.04), and mother’s income per month (t=-2.155, p=0.03). In conclusion, based on the physical activity levels obtained using the accelerometer and steps/day, the majority of the respondents in our study were sedentary. However, the prevalence of sedentary lifestyles was lower when activity levels were assessed using self reported method (GPAQ. Based on multiple linear regression, the physical activity level is related to student’s perceive benefits toward physical activity, individual’s self-efficacy, family support, age and mother income.